2009
DOI: 10.1080/01634370802561877
|View full text |Cite
|
Sign up to set email alerts
|

Examination of a Psychoeducational Intervention and a Respite Grant in Relieving Psychosocial Stressors Associated with Being an Alzheimer's Caregiver

Abstract: Alzheimer's disease can be particularly devastating to those who are caring for their loved one with the condition. There have been recent calls for the tailoring of caregiving interventions to examine outcome differences between groups of caregivers and the reporting of effectiveness via longitudinal and specific outcomes. The purpose of this study was to examine 3 interventions (psychoeducational training, a respite voucher-type grant, or their combination) while looking for possible group differences. A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 25 publications
2
28
1
Order By: Relevance
“…This study fitted well with international findings, such as those of a recent US study (Tompkins & Bell, 2009) on caregivers for people with dementia, which found that psychoeducational interventions improved caregiver outcomes in the form of lower depression scores, increased support service use, and increased support group usage. These improvements were maintained over a 6‐month period despite the continued deterioration in the functional level of the person with dementia (Tompkins & Bell, 2009).…”
Section: Benefits Of Respitesupporting
confidence: 88%
“…This study fitted well with international findings, such as those of a recent US study (Tompkins & Bell, 2009) on caregivers for people with dementia, which found that psychoeducational interventions improved caregiver outcomes in the form of lower depression scores, increased support service use, and increased support group usage. These improvements were maintained over a 6‐month period despite the continued deterioration in the functional level of the person with dementia (Tompkins & Bell, 2009).…”
Section: Benefits Of Respitesupporting
confidence: 88%
“…, Beisecker et al . , Evert & Kukulska , Tompkins & Bell , Phillipson & Jones ,b). Available respite programmes may also be unsuitable for younger persons with dementia and those from culturally and linguistically diverse backgrounds (Alzheimer's Australia's ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It will require improving access to interventions developed to support informal caregivers caring for AD patients and other chronically ill and disabled individuals. Specific strategies include facilitating access to requisite information and supports through expansion of adult day, respite and in-home support programs, caregiver education and training, case management, counseling and care coordination, consumer direction, service integration, chronic disease management, and importantly, evaluation and improvement of programs such as these (Pusey and Richards, 2001;Thompson et al, 2007;Martín-Carrasco et al, 2009;Miller et al, 2009a;Tompkins and Bell, 2009;Olazarán et al, 2010). This is the first study to examine the moderating effect of caregiver burden on the relationship between HUI-III score and institutional service use.…”
Section: Caregiver Distress Scalementioning
confidence: 99%